Road from State to Market-Assessing the Gradual Approach to Banking Sector Reforms in India- - Sayuri Shirai (Asian Development Bank Institute (ADBI), 2002)
Since the initiation of banking sector reforms in 1991, India's highly regulated banking sector has seen significant and favorable changes. Initially, foreign and private sector banks generally outperformed public sector (nationalized and State Bank of India) banks, but such differences have diminished as the latter have improved their performance. However, this does not imply that the reforms have been a total success, for the following reasons. First, public sector banks still remain dominant. In addition, the profitability of nationalized banks has not improved, once interest income from recapitalization bonds is excluded. Second, partial privatization has not significantly improved corporate governance, due to the ceiling of individual voting rights at 10%, the Government's continued dominance as the largest shareholder, and the absence of major reforms determining the boards of directors. Third, priority sector lending still remains a hindrance for the full commercialization of banks. Fourth, banks' large-scale holdings of government securities, while improving their capital adequacy ratios, might crowd out the private sector in the expansionary phase of the economy and lower banks' incentives to improve their risk management skills on lending activities.
hdl:11540/4138
Keywords: 330